Optimizing the Operational Parameters Used in Preparing Anodic Aluminum Oxide (AAO) Templates from Low-purity Aluminum - Lina M. Castro; David Canny; John Henry Castro Posada; Pedronel Araque-Marín; Carlos Ostos (ECS Advances, 2023)
Anodized aluminum oxide (AAO) templates with well-defined geometric pore features and uniform nanoporous arrays were successfully obtained from recyclable low-cost, low-purity (99.16%) aluminum via a two-step anodizing process. The templates were characterized by scanning electron microscopy (SEM) and operating parameters were optimized using a Box-Behnken experimental design. The best conditions were found for an oxalic acid electrolyte concentration of 0.6 M, an anodizing potential of 46 V, and a bath temperature of 10 °C. This process resulted in an averaged regularity ratio (r _avg ) value of 2.66 which compares very favorably with previously reported values obtained from higher-purity aluminum (99.5%). Templates developed from low-purity aluminum are more suitable for high-volume industrial applications where there is a practical trade-off between cost and the quality of the geometric pores.